MODEL KELEMBAGAAN PEMASARAN CABAI MERAH DI KAWASAN SENTRA PRODUKSI PERTANIAN SUMATERA UTARA (MARKETING INSTITUTIONAL MODEL OF RED PEPPER IN NORTH SUMATERA’S AGRICULTURAL CENTRAL PRODUCTION ZONE) - Silvia Darina (Inovasi, 2017)
North Sumatera Province as one of the central areas of agricultural commodity production in Indonesia, with the main commodities produced such as red pepper. This paper aims to develop a policy of institutional development of marketing of red pepper in North Sumatra. Data collection techniques in this study were conducted by interview, direct identification and literature study. The results indicate that the application of agribusiness partnership in agricultural production center in North Sumatera is important in order to achieve product quality according to consumer needs, specialization of activities for efficiency, and public and private partnership in the implementation of agricultural extension. To increase the number and quality of marketing institutions in agricultural production centers in North Sumatra, local governments (provinces and districts / municipalities) through relevant agencies in the region to establish agribusiness units in agricultural production centers involving input traders, farmer groups and traders In agricultural commodity-based areas that are within the control of management and local government (provincial and district / city) in North Sumatra in order to make improvements and development of agricultural commodity marketing system in production center area through development of production information system and commodity market to know data and Information on production, prices and distribution chains to maintain price stability of agricultural production. and improve coordination and synergy for marketing strengthening include: a) developing market information systems (prices, product types, product quality required by consumers); B) maintaining and strengthening existing markets; and, c) promotion in order to capture new markets in both local and regional markets. Keywords: marketing institutional model, red pepper, North Sumatra, production center, agriculture